Morphogenesis of spin cycloids in a noncollinear antiferromagnet - Ojha, Shashank Kumar; Pal, Pratap; Prokhorenko, Sergei; Husain, Sajid; Ramesh, Maya; Li, Xinyan; Kang, Deokyoung; Meisenheimer, Peter; Schlom, Darrell G; Stevenson, Paul; Caretta, Lucas; Nahas, Yousra; et al. (Proceedings of the National Academy of Sciences - PNAS, 2025)
Pattern formation in spin systems with continuous-rotational symmetry (CRS) provides a powerful platform to study emergent complex magnetic phases and topological defects in condensed-matter physics. However, its understanding and correlation with unconventional magnetic order along with high-resolution nanoscale imaging are challenging. Here, we employ scanning nitrogen vacancy (NV) magnetometry to unveil the morphogenesis of spin cycloids at both the local and global scales within a single ferroelectric domain of (111)-oriented BiFeO , which is a noncollinear antiferromagnet, resulting in formation of a glassy labyrinthine pattern. We find that the domains of locally oriented cycloids are interconnected by an array of topological defects and exhibit isotropic energy landscape predicted by first-principles calculations. We propose that the CRS of spin-cycloid propagation directions within the (111) drives the formation of the labyrinthine pattern and the associated topological defects such as antiferromagnetic skyrmions. Unexpectedly, reversing the as-grown ferroelectric polarization from [[Formula: see text][Formula: see text][Formula: see text]] to [111] produces a noncycloidal NV image contrast which could be attributed to either the emergence of a uniformly magnetized state or a reversal of the cycloid polarity. These findings highlight that (111)-oriented BiFeO is not only important for studying the fascinating subject of pattern formation but could also be utilized as an ideal platform for integrating novel topological defects in the field of antiferromagnetic spintronics.